2023
DOI: 10.1021/acs.langmuir.3c01879
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Adsorption Performance of Gases in Oil on a Cr3-Modified SnS2 Monolayer Based on the First Principles

Yu Zhang,
Weiquan Feng,
Jiaqi Zhang
et al.

Abstract: Dissolved gas analysis (DGA) is the most commonly used transformer fault diagnosis technology at present. In this paper, according to the method of first principles of density function theory (DFT), the gas-sensitive mechanisms of four oilsoluble characteristic gases (H 2 , CO, C 2 H 2 , C 2 H 4 ) on intrinsic SnS 2 and Cr 3 −SnS 2 were studied. The adsorption energy and electron transfer were calculated, and the density of states, energy bands, and recovery times were analyzed. It was concluded that H 2 and C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 67 publications
0
1
0
Order By: Relevance
“… However, the potential application of monolayer TiSe 2 as a gas sensing material has not been explored. And it has been shown that defect, doping, , adsorption, , heterojunction, , and applied strain can enhance the surface properties of the material, for example, the use of nanosheets with defective tin selenium to improve sensitivity to the adsorption of SO 2 molecules . Doping with transition metals in GaN nanosheets or MoTe 2 monolayer has also been shown capable of improving sensitivity toward adsorbing NO 2 , and modification with metals in silicon carbide nanosheets or phosphorene to improve the sensitivity to the adsorption of NH 3 molecules. , For the conventional doping and modification of materials, noble metals are generally chosen.…”
Section: Introductionmentioning
confidence: 99%
“… However, the potential application of monolayer TiSe 2 as a gas sensing material has not been explored. And it has been shown that defect, doping, , adsorption, , heterojunction, , and applied strain can enhance the surface properties of the material, for example, the use of nanosheets with defective tin selenium to improve sensitivity to the adsorption of SO 2 molecules . Doping with transition metals in GaN nanosheets or MoTe 2 monolayer has also been shown capable of improving sensitivity toward adsorbing NO 2 , and modification with metals in silicon carbide nanosheets or phosphorene to improve the sensitivity to the adsorption of NH 3 molecules. , For the conventional doping and modification of materials, noble metals are generally chosen.…”
Section: Introductionmentioning
confidence: 99%